South East Europe, No. 9, Spring 2016 : Rebalancing for Stronger Growth - World Bank Group (World Bank, Washington, DC, 2016)
Growth in the six South East European countries (SEE6) rebounded to 2.1 percent in 2015, as investment revived. The SEE6 region is not only growing but also rebalancing to more durable sources of growth. While higher growth in 2015 brought new jobs in the private sector, and helped poverty reduction to resume, unemployment is still entrenched. In 2015, fiscal deficits continued to narrow in all SEE6 countries except Montenegro. With inflation at historic lows, accommodative monetary policy supported growth, and credit to the economy slowly began to grow. The near-term baseline outlook for the region is positive. Fiscal and current account deficits must decline further to support growth. Sustaining the nascent rebalancing requires unlocking the growth potential of the SEE6 economics by reversing productivity dynamics that have been deteriorating since 2008. The agenda for reducing the structural rigidities that impede growth is broad based and centered on five pillars: eliminate disincentives and barriers to formal; employment; improve the business climate and governance; reduce the size of government while improving quality of service delivery; deepen trade and financial integration; and ensure that natural resource use is sustainable.